Respuesta :

Answer:

(6,-3)

or

x=6 y= -3

Step-by-step explanation:

Taking a quick look at this question we notice that we simply cannot add/subtract the two equations and eliminate a variable

What we can do is mulitply an equation to make the above true

let's try to get the first equation to have a 3y, and we can do this by multiplying it by 1.5 (this is legal because we do it to both sides)

So our new first equation is

1.5(3x+2y)=12*1.5

which simplifies to

4.5x+3y=18

We then add the two equatiosn

(4.5x+3y)+(2x-3y)=18+21

6.5x=39

x=6

Now that we know x we can plug that in and solve for y

3(6)+2y=12

18+2y=12

-6=2y

y= -3